2012
DOI: 10.1101/cshperspect.a012195
|View full text |Cite
|
Sign up to set email alerts
|

The Central Amygdala and Alcohol: Role of  -Aminobutyric Acid, Glutamate, and Neuropeptides

Abstract: Alcohol dependence is a chronically relapsing disorder characterized by compulsive drug seeking and drug taking, loss of control in limiting intake, and the emergence of a withdrawal syndrome in the absence of the drug. Accumulating evidence suggests an important role for synaptic transmission in the central amygdala (CeA) in mediating alcohol-related behaviors and neuroadaptative mechanisms associated with alcohol dependence. Acute alcohol facilitates g-aminobutyric acid-ergic (GABAergic) transmission in CeA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 147 publications
(149 reference statements)
7
110
0
2
Order By: Relevance
“…Because mGlu2/3 receptors act as autoreceptors on glutamate terminals (see previous discussion), this indicator of increased mGlu2/3-receptor function does not easily explain the results of in vivo microdialysis and electrophysiological studies indicating greater glutamate sensitivity within the CeA during alcohol withdrawal in dependent animals (cf. Roberto et al, 2012). Moreover, although several reports indicate an elevation in basal and/or alcohol-stimulated glutamate release within forebrain structures, including the NAC (see earlier discussion), Kufahl et al (2011) reported no changes in G protein coupling to mGlu2/3 receptors within either the prefrontal cortex or NAC during alcohol withdrawal in dependent animals.…”
Section: Group 1 Mglursmentioning
confidence: 93%
See 2 more Smart Citations
“…Because mGlu2/3 receptors act as autoreceptors on glutamate terminals (see previous discussion), this indicator of increased mGlu2/3-receptor function does not easily explain the results of in vivo microdialysis and electrophysiological studies indicating greater glutamate sensitivity within the CeA during alcohol withdrawal in dependent animals (cf. Roberto et al, 2012). Moreover, although several reports indicate an elevation in basal and/or alcohol-stimulated glutamate release within forebrain structures, including the NAC (see earlier discussion), Kufahl et al (2011) reported no changes in G protein coupling to mGlu2/3 receptors within either the prefrontal cortex or NAC during alcohol withdrawal in dependent animals.…”
Section: Group 1 Mglursmentioning
confidence: 93%
“…When assayed by in vivo microdialysis, the effects of intraperitoneal (IP) injections of alcohol upon mesocorticolimbic glutamate levels are biphasic with respect to dose; lower doses tend to elevate, whereas higher doses either do not affect or reduce glutamate levels (e.g., Ding, Engleman, Rodd, & McBride, 2012;cf. De Witte, Pinto, Ansseau & Verbanck, 2003;Olive and Becker, 2008;Roberto et al, 2012). Repeated administration of alcohol IP elicits a progressive increase in the capacity of alcohol to stimulate glutamate release, and this alcohol-induced sensitization is well characterized for striatal structures (e.g., Carrara-Nascimento, Griffin, Pastrello, Olive, & Camarini, 2011;Chandler et al, 2006;Melendez, Hicks, Cagle, & Kalivas, 2005;.…”
Section: Glutamate Release / Uptakementioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, the central nucleus of the amygdala (CeA) is considered critical in mediating the behavioral effects of ethanol (Eckardt et al, 1998;Pich et al, 1995;Rassnick et al, 1993;Roberts et al, 1996). In particular, alcohol dependence is defined by the emergence of a negative emotional state mediated in part by the recruitment of pro-and antistress peptides in the amygdala (Koob, 2008;Koob and Le Moal, 2008;Roberto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Permanent changes in the brain may induce relapses to drug abuse long after detoxification. Gamma-aminobutyric acid (GABA)-ergic system and the glutamatergic system play important role in alcohol withdrawal 13 . Increased glutamatergic NMDA function is involved in seizures and cell death.…”
Section: Physical Withdrawalmentioning
confidence: 99%